Different left ventricular remodelling patterns and clinical outcomes between non-ischaemic and ischaemic aetiologies in heart failure patients receiving sacubitril/valsartan treatment. Issue 2 (29th October 2020) - Lee, Ying-Hsiang; Chiou, Wei-Ru; Hsu, Chien-Yi; Lin, Po-Lin; Liang, Huai-Wen; Chung, Fa-Po; Liao, Chia-Te; Lin, Wen-Yu; Chang, Hung-Yu
Abstract: Aims: Although the beneficial effect of sacubitril/valsartan (SAC/VAL) compared to enalapril was consistent across ischaemic cardiomyopathy (ICM) and non-ischaemic cardiomyopathy (NICM) groups, the PARADIGM-HF study did not analyse the effect of ventricular remodelling on patients with different aetiologies, which may affect clinical treatment outcomes. This study aimed to compare left ventricular ejection fraction (LVEF) following SAC/VAL treatment and its association with clinical outcomes. Methods and results: A total of 1576 patients were analysed. Patients were grouped by LVEF changes following SAC/VAL treatment for 8-month period. LVEF improvement ≥15% was defined as 'significant improvement', and <5% or worse was classified as 'lack of improvement'. The primary outcome was a composite of cardiovascular death and unplanned hospitalization for heart failure. Patients with NICM had lower baseline LVEF but improvement was significantly greater comparing to those with ICM (baseline 28.0 ± 7.7% vs. 30.1 ± 7.1%, P  <   0.001, LVEF increase of 11.1 ± 12.6% vs. 6.7 ± 10.2%, P  <   0.001). The effect of functional improvement of SAC/VAL on NICM patients showed bimodal distribution. Primary endpoints were inversely associated with LVEF changes in NICM patients: adjusted hazard ratio was 0.42 [95% confidence interval (CI) 0.31–0.58, P  <   0.001] for NICM patients with significant improvement, and was 1.73 (95% CI 1.38–2.16, P  <   0.001) for NICM patients but lack of improvement. Primary endpoints of ICM patients did not demonstrate an association with LVEF changes. Conclusion: Patients with NICM had higher degree of LVEF improvement than those with ICM following SAC/VAL treatment, and significant improvement of LVEF in NICM patients indicates favourable outcome.